Is ICT mature for an EU‐wide Intelligent Transport System?. Issue 1 (1st March 2013) - Pagano, Paolo; Petracca, Matteo; Alessandrelli, Daniele; Salvadori, Claudio
Abstract : In this study, the general problem of scalable and inter‐operable Intelligent Transport Systems (ITSs) is addressed. Referring to a new proposal based on next generation networks promoting a pervasive, distributed and inter‐operable service‐oriented architecture, the authors comment on existing frontier technologies capable of deploying such systems. A new layered architecture for an EU‐wide ITS is shown against the state‐of‐the‐art ITS design; the presented solution is expected to overcome the actual limitations in pervasiveness of the collection layer and in virtualisation of users, connectivity, storage and calculus. The IPv6 global network (and especially the 6LoWPAN extension to embedded constrained devices), also delivered through wideband technologies, is seen as the enabling technology to support large‐scale ITS; moreover a proposal to explicitly consider distributed calculus and high capacity storage for data and computationally intensive applications is presented.